PENERAPAN MODEL PEMBELAJARAN INKURI TERBIMBING PADA MATERI SIFAT-SIFAT CAHAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI BALFAI KABUPATEN KUPANG - Rohi, Alvi Tama; Ratu, Kurniayu T.R.A; Nawa, Netty E.A. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Thesis by Alvi Tama Rohi, NIM. 2101140131, Elementary School Teacher Education Program, 2026, titled “The Application of the Guided Inquiry Learning Model on the Topic of the Properties of Light to Improve the Learning Outcomes in class V at SD Negeri Balfai Kabupaten Kupang”. The research question is: How does the application of the guided inquiry learning model in the topic of the properties of light improve the learning outcomes in class V at SD Negeri Balfai? This study aims to determine the improvement in the learning outcomes in class V at SD Negeri Balfai Kabupaten Kupang on the topic of the properties of light by using the guided inquiry learning model. The data collection techniques used were observation, testing, and documentation. The subjects of this study were 28 students in Class VA. The research results show that in Cycle I, 9 students (32%) achieved mastery. This was due to the students’ active participation during lessons, their understanding of the material, good group cooperation, and their ability to answer test questions. Meanwhile, 19 students (68%) did not achieve mastery due to a lack of concentration and difficulty in answering test questions. In Cycle II, student learning outcomes improved, with 25 students (89%) achieving mastery because they were more active in listening to and paying attention to the teacher’s explanations, were able to collaborate in groups, and were able to correctly answer test questions. As for the 3 students (11%) who have not yet achieved mastery, they will be provided with remedial and enrichment instruction by the homeroom teacher. Based on the research findings and discussion above, it can be concluded that the implementation of the Guided Inquiry learning model has proven effective in improving student learning outcomes on the properties of light in the class V A at SD Negeri Balfai Kabupaten Kupang. This model encourages students to think critically and discover concepts through hands-on experience, thereby deepening their understanding of the material.